2014
DOI: 10.1530/eje-13-1007
|View full text |Cite
|
Sign up to set email alerts
|

Diverse impacts of aging on insulin resistance in lean and obese women with polycystic ovary syndrome: evidence from 1345 women with the syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) represents a moving spectrum of hormonal to metabolic abnormalities, as women with the syndrome are aging. Hormonal abnormalities, anovulation, and hyperandrogenic signs were predominant during the early years of PCOS and fade away with the years. Metabolic abnormalities and insulin resistance (IR) remain throughout the PCOS life cycle; however, it is unclear as to how they change, as women with the syndrome are aging. Objective: To evaluate the changes in IR and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 47 publications
5
33
0
Order By: Relevance
“…(Boudreaux et al, 2006;Espinos-Gomez et al, 2009;Gambineri et al, 2012). Normal weight women with PCOS have been reported to be insulin resistant (Stepto et al, 2013), but it has also been reported that insulin resistance ameliorates during aging in non-obese women with PCOS, possibly due to decreasing androgen levels (Livadas et al, 2014). We do, however, acknowledge that the numbers of subjects with disturbances of glucose homoeostasis in this subgroup of PCOS women was relatively small.…”
Section: Discussionmentioning
confidence: 68%
“…(Boudreaux et al, 2006;Espinos-Gomez et al, 2009;Gambineri et al, 2012). Normal weight women with PCOS have been reported to be insulin resistant (Stepto et al, 2013), but it has also been reported that insulin resistance ameliorates during aging in non-obese women with PCOS, possibly due to decreasing androgen levels (Livadas et al, 2014). We do, however, acknowledge that the numbers of subjects with disturbances of glucose homoeostasis in this subgroup of PCOS women was relatively small.…”
Section: Discussionmentioning
confidence: 68%
“…We have also showed that circulatory concentrations of TC, TAG, HDL-C, LDL-C, E 2 , SHBG, insulin and HOMA-IR index did not differ between healthy subjects and women with PCOS. It is plausible that age and BMI are the main players in determining the aforementioned biochemical and hormonal features; therefore, differences in the mean age or BMI of patients (in different studies) may lead to inconsistent results, as seen for insulin resistance which is higher in overweight and obese women than in lean individuals (Livadas et al 2014, Moran et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age and serum testosterone of Sarantis Livadas et al study was 32.21 ± 14.40 and 1.36 ± 0.47 nmol/L respectively. (5) Hypoandrogenaemia in men and hyperandrogenaemia in women are associated with increased risk of CAD, but also with visceral obesity, IR, low HDL-C and elevated TG and LDL-C. (17) High testosterone levels are associated with higher risk of type 2 diabetes in women, but with lower risk in men. (18) Therefore, at physiological levels, T and E2 are thought to be involved in maintaining normal insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In a normal population also the aging process is associated with a gradual increase in obesity, IR and β-cell decompensation leading to DM development. (5) Few studies have prospectively examined endogenous sex hormones as predictors of type 2 diabetes in women. (6) Therefore, the relationship of sex hormones producing metabolic and endocrine imbalances associated with lipid profile and IR will contribute to more awareness in terms of sex-and genderspecific risk factors.…”
mentioning
confidence: 99%